Create a firm process safety foundation for your new facilities. Issue 3 (18th March 2016) - Edwards, Victor H.
Abstract : Documented here is the acceptance speech of the 2015 Norton H. Walton‐Russell L. Miller Award of the Safety and Health Division of AIChE. The award was presented to Dr. Victor H. Edwards at the annual division banquet at the Global Congress on Process Safety in Austin, TX on April 28, 2015. The speech emphasizes the crucial role that process safety should play in the concept, siting, and design of process plants. © 2016 American Institute of Chemical Engineers Process Saf Prog 35: 258–259, 2016